Reasons for Dropouts of School Girls: A Study on Saidpur of Nilphamary District (Bangladesh Journal of Public Administration, 2019)
The study was conducted to identify the reasons behind girl‟s dropout from school in rural areas ofBangladesh and understand the problem to find out possible solutions. A questionnaire survey, casestudy and focus group discussion were selected as study instrumentations which were administered atGolna Union of Saidpur Upazila of Nilphamari district. The study identified some socio-cultural andeconomic reasons behind the girl‟s dropout problem. Economic vulnerability of the families was theprimary reason identified behind the problem. Some other problems identified are like dowry, childmarriage, the unemployment problem, tendencies to get a job at Uttara Export Processing Zone(UEZP) and, insufficient cash support for continuing study. Creating job opportunities throughindustrialization and transferring extra agricultural labour were identified as the best possiblesolutions. Also, immediate steps against the dowry system and child marriage, guide book and tuitionstudy system, engaging Non-Government Organizations (NGOs) in development activities have beenrecommended to mitigate the problem. Solving girl‟s dropout problem warrants a holistic approach,engaging all the possible stakeholders to build a quality education system and a socio-economicallytransformed society for the future generation.